2019
DOI: 10.1371/journal.pone.0227065
|View full text |Cite
|
Sign up to set email alerts
|

Glycated albumin as a diagnostic tool in diabetes: An alternative or an additional test?

Abstract: IntroductionStudies have revealed that glycated albumin (GA) is a useful alternative to HbA1c under conditions wherein the latter does not reflect glycaemic status accurately. Until now, there are few studies with non-Asians subjects that report on the validity of GA test in diagnosis of type 2 diabetes mellitus (DM). Thus, the aim of this study was to assess the clinical utility of GA in diagnosis of DM.Materials and methodsThis diagnostic test accuracy study was performed in 242 Brazilian individuals referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“… 16 , 17 Related studies have also confirmed that GA could better reflect patients’ blood glucose fluctuation than HbA1c. 18 , 19 However, blood glucose fluctuation enhances oxidative stress, 20 leading to a decrease in the lifespan of red cells. 21 The greater the MAGE in patients, the higher the peak blood glucose may be, while hyperglycemia can reduce the fluidity of red cell membranes 22 and reduce the lifespan of red cells, decreasing HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Related studies have also confirmed that GA could better reflect patients’ blood glucose fluctuation than HbA1c. 18 , 19 However, blood glucose fluctuation enhances oxidative stress, 20 leading to a decrease in the lifespan of red cells. 21 The greater the MAGE in patients, the higher the peak blood glucose may be, while hyperglycemia can reduce the fluidity of red cell membranes 22 and reduce the lifespan of red cells, decreasing HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…The GA test provides information on the mean blood glucose concentration in the last 15–20 days before blood collection [ 4 , 6 , 8 , 11 , 19 , 24 ].…”
Section: Glycated Albumin (Ga)mentioning
confidence: 99%
“…In addition to the use of HbA1c for the diagnosis of diabetes [ 52 ], the use of additional glycated proteins for this diagnosis and its complications has been widely recommended [ 11 ].…”
Section: Ga and Cardio-metabolic Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations